The Politics of Government-Business Relations in Ghana, 1982-2008 - Opoku, D. author. aut Link
XIV, 264 p.
Keywords: Since the early 1980s, the World Bank, backed by aid donor countries, has been involved in a determined effort to stimulate capitalist growth in Africa by prescribing a set of orthodox, neoliberal economic policies. Using Ghana as a case study, this book considers why this is the case.